On a subclass of starlike functions associated with a strip domain - Kumar, S. Sivaprasad; Verma, Neha (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We introduce a new subclass of starlike functions defined as S^*_τ:={fA:zf’(z)/f(z) 1+z=:τ(z)}, where τ(z) maps the unit disk D:= {zC:|z|<1} onto a strip domain. We deduce structural formulas, as well as the growth and distortion theorems for S^*_τ. In addition, inclusion relations with some well-known subclasses of S are established and sharp radius estimates are obtained, as well as the sharp coefficient bounds for the initial five coefficients and the second and third order Hankel determinants of S^*_τ.